Communication in a virtual environment: from the one-to-one model to the all-to-all model - Lisbôa, Eliana Santana (2011)
The need to know and explain the human communication phenomena lead to the development of many theories and communication models that gradually evolved through time, in accordance with the cultural and sociopolitical contexts. In this article we will address the transformation from models that approached communication through a “one-to-all” logic, allowed by the spread of printed mass media or even radio and television, to a new communication process approach logic that can be resumed in the slogan “all-to-all”. In fact, with de beginning of the Internet and digital technologies, different ways to communicate arise, since, as communication can now reach global amplitude, it favors multiple user connections, allowing for a multidirectional information flow model, or “all-to-all” model logic.